Cache Supported Efficient Path Planning Technique in VANET - Agarkhed, Jayashree; Pawar, Madhu (International Journal of Advanced Science and Technology, 2019)
In mobile road navigation, an important aspect is one that finds consistency between source and destination. Transport Special Network called Vehicular Ad-hoc Network (VANET) is a modern technology that combines the capabilities of next-generation wireless networks in vehicles. The skill of the path planning function is censored due to various scenarios, such as sudden change of direction, unexpected traffic conditions, lack of GPS signals, etc. Another important technology called Intelligent Transport System (ITS) which play an essential role in VANET. In particular, an efficient cache path planning method using the OCVRP (Vehicle Routing Protocol) algorithm with optimal cache support responds to another route planning request. In real time by properly organizing caching and reusing old polled paths. Unlike the traditional cache, where the polled path is used only when the request matches the most recent one. As a result, the server only calculates unmatched paths, which minimizes load of system.